Graphene oxide single sheets as substrates for high resolution cryoTEM. Issue 7 (17th December 2014) - van de Put, Marcel W. P.; Patterson, Joseph P.; Bomans, Paul H. H.; Wilson, Neil R.; Friedrich, Heiner; van Benthem, Rolf A. T. M.; de With, Gijsbertus; O'Reilly, Rachel K.; Sommerdijk, Nico A. J. M.
Abstract : Ultra thin films prepared on single sheet graphene oxide substrates to enhance contrast and resolution in high resolution cryoTEM. Abstract : CryoTEM is an important tool in the analysis of soft matter, where generally defocus conditions are used to enhance the contrast in the images, but this is at the expense of the maximum resolution that can be obtained. Here, we demonstrate the use of graphene oxide single sheets as support for the formation of 10 nm thin films for high resolution cryoTEM imaging, using DNA as an example. With this procedure, the overlap of objects in the vitrified film is avoided. Moreover, in these thin films less background scattering occurs and as a direct result, an increased contrast can be observed in the images. Hence, imaging closer to focus as compared with conventional cryoTEM procedures is achieved, without losing contrast. In addition, we demonstrate an ∼1.8 fold increase in resolution, which is crucial for accurate size analysis of nanostructures.